RESULTS OF THE CONTROL RANDOMIZED STUDIES IN 2009: WHAT IS NEW IN CARDIOLOGY - S. Yu. Martsevich; Yu. V. Lukina (Рациональная фармакотерапия в кардиологии)
Results of the control randomized studies in 2009: what is new in cardiology.